2014
DOI: 10.1177/2325957414555228
|View full text |Cite
|
Sign up to set email alerts
|

Adherence among Rural HIV-Infected Patients in the Deep South

Abstract: Treatment-experienced patients enrolled in ADAP are less likely to be adherent. A QD PI-based MTR may result in comparable adherence to an STR in a rural HIV-infected population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 41 publications
0
27
1
Order By: Relevance
“…In two observational studies, no difference was found between STR and other single-dose MTR among patients initiating ART [24] or among those who switched from STR to MTR for cost reasons [25]. Further complicating drawing conclusions from this literature are findings from a recent study by Tennant et al [26], in which MTR were associated with better adherence than STR based on clinic refill records.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two observational studies, no difference was found between STR and other single-dose MTR among patients initiating ART [24] or among those who switched from STR to MTR for cost reasons [25]. Further complicating drawing conclusions from this literature are findings from a recent study by Tennant et al [26], in which MTR were associated with better adherence than STR based on clinic refill records.…”
Section: Introductionmentioning
confidence: 99%
“…If patients with lower anticipated adherence had a higher tendency of being assigned STR, the improvement in adherence brought by STR might have been attenuated. Variations in measures of adherence across studies may also account for discrepancies in the literature [17, 2022, 24] [16] [26] [18, 19]. Taken together, the inconsistent relationship between STR and adherence obscures inferences that we can draw about the role of treatment simplification on adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Ingredients (2, 3 Table 4 summarizes methods for measuring adherence that were used in the selected articles (n = 67). Most of the studies (n = 62; 93%) relied only on one method; however, five studies [35,50,59,79,82] combined two different methods to assess medication adherence. The applied methods could be divided into two broad categories: subjective (e.g., patient interviews and self-reporting) and indirect (e.g., pill counts, methods using prescription fills, electronic monitoring) [75].…”
Section: Results (Number Of Studies With a Certain Feature) Referencesmentioning
confidence: 99%
“…High adherence: MPR > 0.8 n = 30 [5,[31][32][33]36,[39][40][41]43,44,[49][50][51]54,55,57,58,60,[62][63][64]67,80,82,84,86,89,91,94,95] Proportion of days covered (PDC) General…”
Section: Study-specific/ General Short Description Assessment Of Levementioning
confidence: 99%
See 1 more Smart Citation